Argentina : Economic Developments; April 29, 2015. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2016)
This paper presents an overview of Argentina's economic developments in the past 10 years. Argentina's impressive growth over the past decade has been accompanied by the accumulation of a number of major vulnerabilities. Policy inconsistencies were exposed in early 2014 when mounting balance-of-payments pressures culminated in a sharp devaluation of the peso. Subsequent to the devaluation, domestic imbalances were exacerbated by a deteriorating external environment. At the same time, the dispute with holdout creditors continued to impede Argentina's access to international capital markets. The combination of weak external demand, fast eroding competitiveness, and compromised access to international capital markets fueled balance of payments pressures in 2014.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet